Cinética de reacción de hidrógeno con zry-4 - Fernández, Guillermo E. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2000)
Fil. Fernández, Guillermo E.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina